Clarification of Orange Press Liquors by PVDF Hollow Fiber Membranes - Silvia Simone; Carmela Conidi; Claudia Ursino; Alfredo Cassano; Alberto Figoli (Membranes, 2016)
Press liquors are typical by-products of the citrus juice processing characterized by a high content of organic compounds and associated problems of environmental impact, which imply high treatment costs. However, these wastes contain a great number of health promoting substances, including fibers, carotenoids and phenolic compounds (mainly flavonoids), whose recovery against waste-destruction technologies is very attractive for new business opportunities. In this work, the clarification of orange press liquor by using microfiltration (MF) membranes is studied as a preliminary step to obtain a permeate stream enriched in antioxidant compounds which can be further processed to produce extracts of nutraceutical and/or pharmaceutical interest. MF poly(vinylidene fluoride) (PVDF) hollow fibers were prepared by the dry/wet spinning technique. A series of fibers was produced from the same polymeric dope, in order to investigate the effect of selected spinning parameters, i.e., bore fluid composition and flowrate, on their properties. The morphology of the produced fibers was analyzed by Scanning Electron Microscopy (SEM). Fibers were further characterized for their mechanical properties, porosity, bubble point, pore size distribution and pure water permeability (PWP). Some of the produced fibers exhibited high permeability (pure water permeability ~530 L/m2·h·bar), coupled to good mechanical resistance and pore size in the range of MF membranes. These fibers were selected and used for the clarification of press liquor from orange peel processing. In optimized operating conditions, the selected fibers produced steady-state fluxes of about 41 L/m2·h with rejections towards polyphenols and total antioxidant activity of 4.1% and 1.4%, respectively.